Escherichia coli virulence patterns may help to predict vesicoureteral reflux in paediatric urinary tract infections. (29th July 2015) - Hogan, Julien; Mahjoub, Farah; Larakeb, Anis Skander; Vu Thien, Hoang; Hosany, Ahmad; Bensman, Albert; Grimprel, Emmanuel; Bingen, Edouard; Bonacorsi, Stéphane; Ulinski, Tim
Abstract Aim Ultrasound and biological tools are used to predict high‐grade vesicoureteral reflux, but other markers are needed to better select patients who need voiding cystography. Our aim was to determine whether studying Escherichia coli virulence factors would help to predict vesicoureteral reflux in patients with their first acute pyelonephritis. Methods We included children presenting with E. coli‐related acute pyelonephritis or cystitis. Vesicoureteral reflux was assessed by voiding cystography. Virulence factors were identified by multiplex polymerase chain reaction. Statistical analysis was performed using logistic regression and the mean c‐statistic test. Results We included 198 patients: 30 with cystitis and 168 with acute pyelonephritis, including 46 with vesicoureteral reflux. High‐grade reflux was associated with acute pyelonephritis caused by the E. coli lacking virulence factors papGII (82% versus 47%, p < 0.001) or papC (85% versus 53%, p < 0.001) or belonging to phylogenetic group A or B1. When we added genetic data (lack of papGII, fyuA and phylogenetic groups) to classical predictors of vesicoureteral reflux (ultrasound examination, gender, age), the ability to predict high‐grade reflux increased, with the c‐statistic rising from 0.88 to 0.93. Conclusion Bacterial virulence factors and clinical factors helped to predict high‐grade reflux and may help to avoid unnecessary voiding cystographies.